2022
DOI: 10.1021/acs.inorgchem.2c03337
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Approach to Carbodiphosphorane–Bismuth Coordination Chemistry: Cationization, Redox-Flexibility, and Stabilization of a Crystalline Bismuth Hydridoborate

Abstract: Bismuth complexes stabilized by carbon-based donor ligands are underserved by their instability, often due to facile ligand dissociation and deleterious protonolysis. Herein, we show that the ortho-bismuthination of hexaphenylcarbodiphosphorane enables a robust framework with geometrically constrained carbone–bismuth bonding interactions, which are highly tunable by cationization. The carbodiphosphorane bismuth halides (1 and 2) are remarkably air-stable and feature unprecedented trans carboneC–Bi–X ligation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…1 + was prepared using a similar methodology recently reported by Sundermeyer, which showed that hexaphenyl-carbodiphosphorane can be doubly deprotonated by n BuLi, producing a dilithiated hexaphenyl-carbodiphosphorane ligand, which can be used as a dianionic tridentate CCC pincer-type ligand. , Thus, hexaphenyl-carbodiphosphorane ( 2 ) was treated with 2 equiv of n BuLi followed by addition of PCl 3 , which resulted in precipitation of the desired [ 1 + ]­[Cl] (Scheme ). The 31 P NMR of [ 1 + ]­[Cl] in CDCl 3 was measured, showing two broad singlets with chemical shifts of δ = 29.80 and 54.24 ppm with the integration ratio of 2:1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 + was prepared using a similar methodology recently reported by Sundermeyer, which showed that hexaphenyl-carbodiphosphorane can be doubly deprotonated by n BuLi, producing a dilithiated hexaphenyl-carbodiphosphorane ligand, which can be used as a dianionic tridentate CCC pincer-type ligand. , Thus, hexaphenyl-carbodiphosphorane ( 2 ) was treated with 2 equiv of n BuLi followed by addition of PCl 3 , which resulted in precipitation of the desired [ 1 + ]­[Cl] (Scheme ). The 31 P NMR of [ 1 + ]­[Cl] in CDCl 3 was measured, showing two broad singlets with chemical shifts of δ = 29.80 and 54.24 ppm with the integration ratio of 2:1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These challenges have been met by the use of chelating ligands, bulky ligands with π‐donating abilities, and weakly coordinating anions [36–38, 51] . Very recently, the reversible protonation of a dianionic ligand at its carbodiphosphorane functional group has been reported as a new access to cationic bismuth compounds [64] …”
Section: Synthesismentioning
confidence: 99%
“…These challenges have been met by the use of chelating ligands, bulky ligands with π‐donating abilities, and weakly coordinating anions [36–38, 51] . Very recently, the reversible protonation of a dianionic ligand at its carbodiphosphorane functional group has been reported as a new access to cationic bismuth compounds [64] …”
Section: Synthesismentioning
confidence: 99%